PENGARUH PUCUK DAUN KACANG PANJANG (VIGNA SINENSIS) TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM KLINIK ALISAH TREISYA DI KOTA MEDAN TAHUN 2022 - Mutiara Dwi Yanti; VITRILINA HUTABARAT; dosma sinta roha; septa dwi insani (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
insufficient breast milk production is the primary cause why mothers cease breastfeeding early. The content of cypinone and polyphenol compounds within the leaves of lengthy beans (Vigna Sinensis L) has a lactation effect, so it can growth breast milk secretion and stimulate breast milk. This examine aimed to reveal the impact of feeding babies with long-leaf bean sprouts on growing lactation in postpartum mothers. This form of take a look at is a semi-experimental examine with a pre-test and publish-check group. A sample of 16 postpartum mothers who met the inclusion and exclusion criteria received postnatal mothers up to 250 g for 7 days. The device used become a survey. This observe was conducted the use of Wilcoxon's take a look at, and it changed into discovered that contributors who have been fed lengthy bean sprouts have been capable of growth their milk production by using 75%, which is sufficient for a 25% boom. The results of the analysis reached p 0.000 (p £ 0.05) indicating an increase in postnatal breast milk manufacturing. it could be concluded that the leaves of fenugreek which might be saved for a long term can increase lactation in postpartum mothers.